Pengembangan Manajemen Layanan Perpustakaan Berbasis Aplikasi “UMMA PANDE” untuk Meningkatkan Literasi Membaca Siswa SD Negeri Weetabula II, Sumba Barat Daya - Bulu, Vera Rosalina; Meok, Nixon J; Masi, Lolang Maria; Manu, Yubelvi; Tnunay, Samuel (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program was carried out at SDN Weetabula II, Sumba Barat Daya, which faced problems of low reading interest among students, limited book collections, and manual library management. These conditions resulted in less optimal library services and limited literacy development. The aim of this activity was to develop the UMMA PANDE application as a digital-based library management system to improve access to reading materials and management efficiency. The methods included needs assessment, application design, system implementation, training for teachers and library staff, and evaluation assistance. The results indicated improved collection management, faster book borrowing and returning services, and increased student reading interest due to easier and more engaging access. In conclusion, the UMMA PANDE application provides an effective and innovative solution to overcome library management limitations while supporting literacy improvement in the digital era.